Non‐invasive clinical and microscopic evaluation of the response to treatment with clobetasol cream vs. calcipotriol/betamethasone dipropionate foam in mild to moderate plaque psoriasis: an investigator‐initiated, phase IV, unicentric, open, randomized clinical trial. (6th July 2020) - Yélamos, O.; Alejo, B.; Ertekin, S. S.; Villa‐Crespo, L.; Zamora‐Barquero, S.; Martinez, N.; Domínguez, M.; Iglesias, P.; Herrero, A.; Malvehy, J.; Puig, S.
Abstract: Background: Treatment response for psoriasis is typically evaluated using clinical scores. However, patients can relapse after clinical clearance, suggesting persistent inflammation. Dermoscopy, reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) can non‐invasively improve treatment response assessment. Objectives: To compare the clinical and non‐invasive microscopic features in a psoriatic target lesion treated with clobetasol cream or calcipotriol/betamethasone dipropionate foam (Cal/BD foam). Methods: Prospective, unicentric, open, randomized clinical trial comparing clinical data [total clinical score (TCS)] and microscopic data (dermoscopy, RCM and OCT) in psoriasis patients treated with clobetasol or Cal/BD foam. Results: We included 36 adult patients (22 men). At week 4, more patients treated with Cal/BD foam achieved TCS ≤1 than with clobetasol (63.2% vs. 18.8%, P = 0.016). Treatment satisfaction was higher with Cal/BD foam ( P < 0.03). Microscopically, Cal/BD foam induced more reduction in epidermal thickness at week 4 ( P < 0.049). Dilated horizontal blood vessels were more common with clobetasol than with Cal/BD foam at week 8 (69.2% vs. 31.2%, P = 0.159). If epidermal hyperplasia was noted at baseline, the response was poorer with clobetasol ( P = 0.029). Limitations: Small sample size, open study, imaging sampling bias. Conclusion: Cal/BD foam is more effective than clobetasol, has better patient satisfaction and induces greater reduction in the hyperkeratosis/acanthosis, regardless of baseline epidermal hyperplasia.